2020
DOI: 10.1016/j.exphem.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis and inflammation: Partners in leukemogenesis and comorbidity

Abstract: Clonal hematopoiesis (CH) of indeterminate potential (CHIP), defined as the presence of a somatic mutation in the peripheral blood at a variant allele frequency (VAF) ≥2%, affects at least 10% of individuals older than 65, but low-VAF clones can be detected in 95% of individuals older than 50. CHIP associates with a wide range of comorbidities from atherosclerosis to pulmonary disease. A growing body of evidence, primarily from studies involving Tet2-knockout and stem cell transplant models of CH, suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 93 publications
1
99
0
2
Order By: Relevance
“…Most reports use a VAF of at least 2% to define CHIP, which represents the sensitivity threshold of current HTS technologies used in the clinical setting [20]. Sequencing data variability and threshold of our HTS technology were determined by serial sequencing of the multiplex NGS Tru-Q DNA 7 (Horizon Diagnostics, Cambridge, UK).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Most reports use a VAF of at least 2% to define CHIP, which represents the sensitivity threshold of current HTS technologies used in the clinical setting [20]. Sequencing data variability and threshold of our HTS technology were determined by serial sequencing of the multiplex NGS Tru-Q DNA 7 (Horizon Diagnostics, Cambridge, UK).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…The underlying mechanisms of the link between CHIP and cardiovascular diseases are being sought in cardiovascular research. It has been suggested that CHIP associated mutations can alter transcription of genes related to in ammatory pathways in peripheral blood cells such as monocytes, potentially augmenting in ammatory responses during the atherogenesis (10). Murine models of TET2 and DNMT3A loss-of-function mutations showed advanced cardiovascular diseases, potentially through accelerating in ammation (31).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on CHIP (7-9) have focused on late stages of atherosclerosis and there is a lack of data to show the impact of CHIP on endothelial dysfunction, which can also be impaired by prevalent in ammation. Yet, patients with mutations in DNMT3A or TET2 are at higher risk of cardiovascular diseases, which is linked to IL-6 receptor activation (10,11). TET2 de cient-cells have also showed increased transcription of IL-6 via alternation in histone deacetylation (12).…”
Section: Introductionmentioning
confidence: 99%
“…In more than half of them, death was caused by adverse events, such as infection and the development of a therapy-related neoplasm. It is interesting to note that the association between CHIP and inflammation is not confirmed for every inflammatory condition, e.g., RA, which could indicate a potential role of anti-inflammatory drugs in suppressing CH [17]. Therefore, further examination of the complex biological processes (responsible for both conditions) could lead to a better understanding of the clinical pathologies, thus increasing the possibility of adopting a specialized medicine approach.…”
Section: Pathophysiology Of the Connection Between Aid And Lymphomamentioning
confidence: 99%